GENDER STEREOTYPES IN CHILDREN'S UPbringing AND THEIR IMPACT ON THE THINKING OF PRESCHOOL CHILDREN (Universal International Scientific Journal, 2026)
This article discusses the thinking of preschool children and its development, manifestations, and the stages of the emergence of concepts and imagination.
Keywords: thinking, child, development, analysis, reasoning.